Pemberdayaan Ekonomi Indonesia Melalui Investasi Wakaf Produktif Dompet Dhuafa - Aisyah Sayidul Lintang; Ali Hamdan (International Conference on Islamic Economic (ICIE), 2024)
Economic empowerment is one of the strategies to improve the economy and equalize the economy in all regions of Indonesia. This empowerment concept aims to support Indonesian people to be productive and valid for the long term and sustainably. Economic empowerment through waqf investment is a concept that can have a positive impact on development. society, especially in the social and economic fields of economic empowerment in Indonesia, Waqf itself is a donation or property given by individuals or groups for the public interest. Waqf investment has great potential to empower the economy through various projects that support holistic community development. It is important to involve various parties, including the government, financial institutions, and the community, in the planning and implementation of waqf investment projects. This research took data samples from one of the waqf management institutions, namely Dompet Dhuafa and managed using qualitative methods. This research aims to educate and provide in-depth literacy regarding Indonesian economic empowerment through waqf investments managed by Dompet Dhuafa. Keywords: Economic Empowerment, Waqf Investment, Dompet Dhuafa Abstrak : Pemberdayaan ekonomi menjadi salah satu strategi untuk meningkatkan perekonomian dan pemerataan ekonomi di seluruh daerah Indonesia, konsep pemberdayaan ini mengarah untuk mensupport masyarakat Indonesia menjadi produktif dan dan berlaku untuk jangka panjang serta berkelanjutan, pemberdayaan ekonomi melalui investasi wakaf adalah suatu konsep yang dapat memberikan dampak positif dalam pengembangan masyarakat terutama dalam bidang sosial dan ekonomi pemberdayaan ekonomi di Indonesia, Wakaf sendiri adalah sumbangan atau harta yang diberikan oleh individu atau kelompok untuk kepentingan umum, Investasi wakaf memiliki potensi besar untuk memberdayakan ekonomi melalui berbagai proyek yang mendukung pembangunan masyarakat secara holistik. Penting untuk melibatkan berbagai pihak, termasuk pemerintah, lembaga keuangan, dan masyarakat, dalam perencanaan dan pelaksanaan proyek investasi wakaf. penelitian ini mengambil sampel data dari salah satu lembaga pengelola wakaf yaitu Dompet Dhuafa dan dikelola dengan metode kualitatif, penelitian ini ditujukan untuk mengedukasi dan memberikan literasi secara mendalam terkait pemberdayaan ekonomi Indonesia melalui investasi wakaf yang di kelola Dompet Dhuafa. Kata Kunci: Pemberdayaan Ekonomi; Investasi Wakaf; Dompet Dhuafa